ANALYSIS OF REGISTER IN THE CONVERSATION OF SHORT MOVIE “TIRAKAT” BY SMP AL MUSYAFFA - Widiyanto, Tomy (VARIABLE RESEARCH JOURNAL, 2024)
Movies were at times reflections of the society in which the story took place. “Tirakat” was one of the short movies that had produced by SMP Al Musyaffa due to the admission needs for welcoming new students in the academic year of 2021/2022. The talks of the short movie presents were the value of religion, social, culture, and education that characterized with Jarwo, Tarjo, Ky. Derman, Inem, and Dyah. This research aimed to explore the register of linguistic forms used in the conversation by the main characters in the short movie that each other had unique expressions were highly influencing in the movie, in terms of the linguistic forms which were formal and informal register all characters performed. The result revealed that the registers of linguistic form in the short movie “Tirakat” were influenced by the context of the characters had had communication with the interlocutors. The formal linguistic form of register was used by Inem, Jarwo, and Dyah to Tarjo and Ky Derman who had social level power. In contrary, the informal linguistic forms were used by them. That was when Tarjo had conversation with Inem and Jarwo, Ky Derman to Dyah, and Inem to Jarwo.